2020
DOI: 10.4081/idr.2020.8744
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dengue Virus Serotype 2 in Vero Cells with [Cu(2,4,5-triphenyl-1H-imidazole)2(H2O)2].Cl2

Abstract: Dengue fever and dengue hemorrhagic fever are transmitted to humans by the Aedes aegypti and Aedes albopictus mosquitoes, with an observed 30-fold increase in global incidence the last 50 years. Despite the tremendous efforts invested anti-dengue virus research, no clinically approved vaccine or antiviral chemotherapeutics are available for humans, and disease treatment is limited to supportive care. Over the years there has been a continuous interest in the chemistry of metal complexes with biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Experimental results displayed that the complex showed cytotoxicity (CC 50 ) of about 98.62 μg/ml and inhibition rate (IC 50 ) of nearly 300.36 μg/ml against the Vero cells. The selective index (SI) data showed a value of 1.96, confirming that the complex inhibits the DENV replication with minimum cytotoxicity for the Vero cells [ 112 ].…”
Section: Nitrogen ( N ) - Conta...mentioning
confidence: 99%
“…Experimental results displayed that the complex showed cytotoxicity (CC 50 ) of about 98.62 μg/ml and inhibition rate (IC 50 ) of nearly 300.36 μg/ml against the Vero cells. The selective index (SI) data showed a value of 1.96, confirming that the complex inhibits the DENV replication with minimum cytotoxicity for the Vero cells [ 112 ].…”
Section: Nitrogen ( N ) - Conta...mentioning
confidence: 99%
“…It is known that several drugs contain heavy elements in their chemical composition [121,122] [126]. Sr-based drugs increase bone mass in postmenopausal osteoporosis patients and reduce fracture risk [127][128][129][130][131].…”
Section: Highlighting Heavy Elements In Drugsmentioning
confidence: 99%
“…Copper (II) is a co-factor in the active of superoxide dismutase, which involved in the body antioxidant defenses and the functions of critical immune cells such as T helper cells, B cells, neutrophils natural killer (NK) cells, and macrophages (Raha, Mallick, Basak, & Duttaroy, 2020). In a study, it was determined that a Cu-complex compound had antiviral effect to DENV-2 in Vero cells which are monkey kidney epithelial cell (Sucipto & Martak, 2020). Sucipto and Martakalso reported that Copper (II) dihydrate exhibited a disruption effect on dengue virus replication, DENV-2, in vivo study (Sucipto & Martak, 2020).…”
Section: Copper (Cu)mentioning
confidence: 99%
“…In a study, it was determined that a Cu-complex compound had antiviral effect to DENV-2 in Vero cells which are monkey kidney epithelial cell (Sucipto & Martak, 2020). Sucipto and Martakalso reported that Copper (II) dihydrate exhibited a disruption effect on dengue virus replication, DENV-2, in vivo study (Sucipto & Martak, 2020). Copper (Cu) can significantly reduce the infectious viruses such as bronchitis virus, poliovirus, human immunodeficiency virus type 1(HIV-1).…”
Section: Copper (Cu)mentioning
confidence: 99%